Evolução das globinas nos anfíbios - Queiroz, João Pedro Fernandes (2021)
The globin gene repertoire of gnathostome vertebrates is dictated by differential retention and loss of nine paralogous gene types: androglobin, neuroglobin, globin X, cytoglobin, globin Y, myoglobin, globin E, and the α- and β-globins. We report the globin gene repertoire of three orders of modern amphibians: Anura, Caudata, and Gymnophiona. Combining phylogenetic and conserved synteny analysis, we show that myoglobin and globin E were lost only in the Batrachia clade, but retained in Gymnophiona. The major amphibian groups also retained different paralogous copies of globin X. None of the amphibian presented αD-globin gene. Nevertheless, two clades of β-globins are present in all amphibians, indicating that the amphibian ancestor possessed two paralogous proto β-globins. We also show that orthologs of the gene coding for the monomeric hemoglobin found in the heart of Rana catesbeiana are present in Neobatrachia and Pelobatoidea species we analyzed. We suggest that these genes might perform myoglobin- and globin E-related functions. We conclude that the repertoire of globin genes in amphibians is dictated by both retention and loss of the paralogous genes cited above and the rise of a new globin gene through co-option of an α-globin, possibly facilitated by a prior event of transposition.